2015
DOI: 10.1002/prot.24737
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of HIV protease flexibility by the T80N mutation

Abstract: The flexibility of HIV protease plays a critical role in enabling enzymatic activity and is required for substrate access to the active site. While the importance of flexibility in the flaps that cover the active site is well known, flexibility in other parts of the enzyme is also critical for function. One key region is a loop containing Thr 80 which forms the walls of the active site. Although not situated within the active site, amino acid Thr80 is absolutely conserved. The mutation T80N preserves the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…(B)]. The conclusion (similar to that observed in HIV protease) is that dynamics are responsible for the majority of intensity change observed on IHP binding—and that the molecule is more flexible/dynamic when IHP binds.…”
Section: Resultsmentioning
confidence: 99%
“…(B)]. The conclusion (similar to that observed in HIV protease) is that dynamics are responsible for the majority of intensity change observed on IHP binding—and that the molecule is more flexible/dynamic when IHP binds.…”
Section: Resultsmentioning
confidence: 99%
“…Sigma‐r plots can also be compared with X‐ray solution scattering data by using the method “Vector‐length convolution,” which convoluting the pair correlation function p ( r ) from a calculated rigid scattering pattern by XS and a Gaussian distribution with the half‐width σ = c × r e to predict a more flexible structural ensemble, where r is the vector length of the protein. Sigma‐r plot from X‐ray solution scattering data can be carried out by plotting σ from the best prediction as a function of r , which give us a connection between MD simulation data and experimental observed data.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of sigma‐r plots from WAXS patterns and MD simulations from HIV protease indicated that the protein in solution was undergoing structural fluctuations with length scales much greater than those indicated by the simulations. This observation suggested either that the MD simulations did not reflect a full structural ensemble or that the solution conditions supported far greater structural fluctuations than reflected in the MD trajectories.…”
Section: Introductionmentioning
confidence: 91%
“…Although containing no dynamical information, per se, WAXS data reflect the structural heterogeneity intrinsic to the entire conformational ensemble in solution. Comparison of WAXS from proteins in solution with that predicted for rigid proteins often identifies discrepancies that can be attributed to structural fluctuations and can provide information about the spatial scale and nature of those fluctuations in a manner not possible with SAXS. The Debye formula should, in principle, provide a simple basis for the calculation of solution scattering from atomic coordinates, but accounting for solvent molecules in the hydration layer and the volume of solvent excluded by the protein complicates the calculation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation